Edukasi Dan Pemeriksaan Gula Darah Acak Pada Masyarakat Di Wilayah Kelurahan Kalijudan Kecamatan Mulyorejo Surabaya - Fitrotin Azizah; Anindita Riesti Retno Arimurti; Ellies Tunjung Sari Maulidiyanti; Rahma Widyastuti; Nur Vita Purwaningsih; Eni Sumarliyah (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Sugar disease or diabetes is commonly known in medical terms with diabetes mellitus. Diabetes mellitus is a disease characterized by an increase in blood glucose levels (hyperglycemia) that occurs due to the body's lack of the hormone insulin both absolute and relative. Glucose is a form of carbohydrate metabolism that functions as the main source of energy controlled by insulin. Excess glucose is converted into glycogen which will be stored in the liver and muscles for backup if needed. Increased blood glucose levels occur in patients with Impaired Glucose Tolerance (TGT), Impaired Fasting Blood Sugar (GDPT) and Diabetes Mellitus. Service activities in the form of education related to the dangers of Diabetes Mellitus, the use of natural ingredients as an alternative to lowering sugar levels and checking Random Blood Sugar levels. There is an increase in public knowledge because the post-test value is higher when compared to the pre-test value. The average pre-test score is 38.3 points while the average post-test score is 79.2 points. And the results of the GDA examination stated 23 people whose results were above normal and 13 people whose results were still within the normal range.